Examining the Validity, Reliability, and Measurement Invariance of the Social Support for Exercise Scale Among Spanish- and English-Language Hispanics. Issue 3 (August 2019) - Walker, Timothy J.; Heredia, Natalia I.; Reininger, Belinda M.
The Social Support for Exercise Subscales are commonly used among Hispanic populations. The aims of this study were to test the validity and reliability of the Spanish-language version of the Social Support for Exercise Subscales and test the invariance of the Spanish- and English-language versions. Data were from a subsample of Hispanic adults in the Cameron County Hispanic Cohort ( n = 1, 447). A series of confirmatory factor analysis (CFA) models were used to assess the validity and reliability of the Spanish-language version of the subscales. A multigroup CFA approach was used to test measurement invariance. Results indicated the Spanish-language versions of family and friend support subscales had good validity and reliability, root mean square error approximation (RMSEA) < .07, comparative fit index (CFI) > 0.95, Tucker-Lewis index (TLI) > 0.94, and standardized root mean square residual (SRMR) < 0.05. There was also evidence of measurement invariance between the Spanish- and English-language versions. These findings indicate the Spanish-language family and friend support subscales are valid and can be compared between Spanish- and English-language Hispanic respondents.